Differential inactivation of alcohol dehydrogenase isoenzymes in Zymomonas mobilis by oxygen. - Tamarit, J (1997)
Zymomonas mobilis is endowed with two isoenzymes of fermentative alcohol dehydrogenase, a zinc-containing enzyme (ADH I) and an iron-containing enzyme (ADH II). The activity of ADH I remains fully conserved, while ADH II activity decays when anaerobic cultures are shifted to aerobiosis. This differential response depends on the metal present on each isoenzyme, since pure preparations of ADH I are resistant to oxidative inactivation and preparations of zinc-containing ADH II, obtained by incubation of pure ADH II with ZnCl2, showed no modification of the target for oxidative damage (His277-containing peptide). It was consistently found that the activity of the zinc-containing ADH II, once submitted to oxidative treatment, was fully restored when iron was reintroduced into the enzyme structure. These results indicate that zinc bound to these proteins plays an important role in the protection of their active centers against oxidative damage and may have relevant biochemical and physiological consequences in this species.